Creative practice in a group setting - Argyle, Elaine; Winship, Gary (Emerald, 2015)
Purpose – Involvement in creative practice is commonly regarded as “therapeutic” but what is actually meant by this and how does this work promote social inclusion and mental well-being, particularly when performed in a group setting? Drawing on the findings of a research project called Clay Transformations (AHRC), the purpose of this paper is to consider these questions. The project involved running a series of clay workshops aimed at people with experience of mental health service use and those who work with them.